2015
DOI: 10.7317/pk.2015.39.2.338
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aminated Poly(ether imide) for the Preparation of Bi-polar Membranes and Their Application to Hypochlorite Production through the Surface Direct Fluorination

Abstract: 초록: 폴리페닐렌옥사이드(PPO)와 폴리에테르이미드(PEI)에 대해 각각 설폰화(SPPO) 및 아민화(APEI)반응이Abstract: Poly(phenylene oxide) (PPO) and polyether imide (PEI) were sulfonated and aminated to create sulfonated poly(phenylene oxide) (SPPO) and aminated polyether imide (APEI), respectively. Characterization of the SPPO and APEI were performed via measurements of FTIR, thermogravimetry (TGA), swelling degree, ion exchange capacity (IEC), and ion conductivity. Next, the surfaces of these membranes were modified by surface fluorination at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…To characterize the electric and physical properties of the synthesized SPEEK and APSf, the swelling degree, ion-exchange capacity, and ion conductivity were measured. Measurement procedures followed previously adopted standards. , …”
Section: Methodsmentioning
confidence: 99%
“…To characterize the electric and physical properties of the synthesized SPEEK and APSf, the swelling degree, ion-exchange capacity, and ion conductivity were measured. Measurement procedures followed previously adopted standards. , …”
Section: Methodsmentioning
confidence: 99%
“…Pioneer works by Nazarov et al [ 39 ] and Koros et al [ 40 ] showed a significant impact of the fluorinated layer on liquid permeation through gas-phase fluorinated polyethylene. Later, the direct fluorination technique was applied for treatment of membranes prepared from different classes of polymers in glassy and rubbery states (polyolefins [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], polyacetylenes [ 57 , 58 , 59 ], polyethers [ 60 , 61 , 62 , 63 , 64 , 65 ], polyesters [ 66 ], urethane-based polymers [ 67 ], polyetherketones [ 68 ], polysulfones [ 69 , 70 , 71 ], polyimides [ 72 , 73 , 74 , 75 ], etc.).…”
Section: Chemical Composition and Laminate Structure Of Fluorinated Membranesmentioning
confidence: 99%